2017
DOI: 10.1364/oe.25.033359
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced distributed entanglement in atom-cavity-fiber system

Abstract: The distributed quantum computation plays an important role in large-scale quantum information processing. In the atom-cavity-fiber system, we put forward two efficient proposals to prepare the steady entanglement of two distant atoms with dissipation. The atomic spontaneous emission and the loss of fiber are exploited actively as powerful resources, while the effect of cavity decay is inhibited by quantum Zeno dynamics and quantumjump-based feedback control. These proposals do not require precisely tailored R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Its chemical structure belongs to the hydroxyindole family. In recent years, studies have found that Emo has a wide range of pharmacological effects, mainly anti-tumor, anti-microbial, anti-oxidation, and anti-inflammatory [ 12 15 ]. Modern researches show that Emo extract could significantly inhibit the inflammatory responses in a variety of inflammatory animal models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its chemical structure belongs to the hydroxyindole family. In recent years, studies have found that Emo has a wide range of pharmacological effects, mainly anti-tumor, anti-microbial, anti-oxidation, and anti-inflammatory [ 12 15 ]. Modern researches show that Emo extract could significantly inhibit the inflammatory responses in a variety of inflammatory animal models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its chemical structure belongs to the hydroxyindole family. In recent years, studies have found that Emo has a wide range of pharmacological effects, mainly anti-tumor, anti-microbial, anti-oxidation, and anti-inflammatory [19][20][21][22] . Modern researches show that Emo extract could significantly inhibit the inflammatory responses in a variety of inflammatory animal models [23] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the realization of a purely steady entangled state cannot be ensured by the dissipation alone. Therefore, various manners are combined with the disspation to improve the purity of target state such as purification and feedback control [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. For instance, based on continuous monitoring of quantum jumps, Wang et al [ 29 ] and Mancini [ 30 ] showed that the Markovian feedback scheme is able to increase the steady-state entanglement for two two-level atoms coupled to a single Bosonic mode that is driven and heavily damped.…”
Section: Introductionmentioning
confidence: 99%